Identificación y análisis de riesgos eléctricos en el laboratorio de pruebas de transformadores de la empresa eléctrica Ambato R C N S.A. Propuesta de un manual de procedimiento de trabajo seguro. - Altamirano Correa, Iván Marcelo (2011)
The electric risks are constantly presents in the transformers test laboratory of the Empress Electrical Ambato RCN SA. The most important contents in this thesis are: work related risks, electric risks, physical effects of the electric shock, single and three phase Transformers of distribution, procedures of electric tests in transformers, risks in the transformers tests, identification and evaluation of the electric risks in the laboratory, using the Fine Method, safety rules for electric risks, etc. The purpose is to identify the electric risks in the several procedures of the transformers tests , besides to specify the location of the electric risks inside the tests laboratory thought the study of procedures that develop in this electric work area to create a Safe Work Procedures Handbook to prevent electricity related accidents. The methodology to use basically is bibliographical, documental, descriptive, on the field, and the observation in the same moment that the electrical test is getting done on the transformers. The contribution and importance of this job is to arrange a Safe Work Procedures Handbook with the objective of prevent accidents or incidents caused by the electric current. This kind of investigation is Feasible Project. The beneficiaries of this study are the EEASA laboratory’s personnel, because their normal tasks are accomplished without a written safety procedure, with no necessary cautions required in a work activity like this, with no safety inspections done by the personnel of this area, etc. D